Small RNAs in Aedes aegypti: one giant step for virus control in mosquitoes - Williams, Adeline E., author; Olson, Ken, advisor; Antolin, Mike, committee member; Calvo, Eric, committee member; Franz, Alexander, committee member; Wilusz, Jeffrey, committee member (Colorado State University. Libraries, 2022)
Aedes aegypti mosquitoes are key vectors of medically relevant arthropod-borne (arbo) viruses such as Zika (ZIKV), dengue (DENV1-4), and yellow fever (YFV). When Ae. aegypti become infected with arboviruses, RNA interference (RNAi) is a critical antiviral immune mechanism that is a key determinant for successful virus transmission. The major antiviral pathway is the RNAi small-interfering RNA (siRNA) pathway, although evidence shows that the Piwi-interacting RNA (piRNA) pathway also acts as an important RNAi mechanism for controlling persistently infective viruses. The overarching goals of this work were twofold: (1) to determine the potency of the Ae. aegypti siRNA pathway against Zika virus and (2) to understand molecular mechanisms underlying piRNA-mediated antiviral immunity and its implications on mosquito vector competence. To achieve these goals, we (1) engineered transgenic Ae. aegypti mosquitoes that synthetically triggered the endogenous siRNA pathway against ZIKV and then quantified virus resistance in these mosquitoes, (2) sequenced small RNAs (sRNAs) of the mosquito virome that may impact vector competence and virus persistence, and (3) characterized structural features of Piwi4, an antiviral protein, involved in sRNA binding and subcellular localization to gain insights on its role in the piRNA and siRNA pathways. A major challenge in the fight against arboviruses is the lack of effective vaccines and limited therapeutic options. Vector control remains the primary method of preventing disease, and integrated vector management (IVM), including the genetic control of mosquitoes, is imperative to prevent emerging arboviral diseases. To this end, we designed an antiviral effector gene – a ZIKV-specific double stranded (ds) RNA –that synthetically triggered the mosquito's siRNA pathway after a bloodmeal in transgenic Ae. aegypti. Small RNA analyses in transgenic midguts revealed ZIKV-specific 21 nucleotide (nt) siRNAs 24 hours after a non-infectious bloodmeal. Nearly complete (90%) inhibition of ZIKV replication was found 7-to-14 days post-infection (dpi); furthermore, significantly fewer transgenic mosquitoes contained ZIKV in their salivary glands (p = 0.001), which led to a reduction in the number of ZIKV-containing saliva samples as measured by transmission assay. Our work shows that the siRNA pathway can be synthetically exploited to generate ZIKV-resistant Ae. aegypti mosquitoes. In the context of gene drive, antiviral effectors expressed in transgenic Ae. aegypti will be an invaluable tool for a population replacement vector control approach. piRNA-mediated antiviral immunity involves an endogenous viral element (EVE) – viral derived cDNA (vDNA) integrated into host genomes – as well as infection with a cognate virus, which together trigger piRNA amplification and lead to virus silencing. EVEs are from viruses that infected a population in previous generations, and most are derived from insect-specific viruses (ISVs) that persistently infect Ae. aegypti. We hypothesized that ISVs and ISV-derived piRNA populations, like EVEs, have geographic structure and impact vector competence to arboviruses. To test this hypothesis, we sequenced sRNAs from geographically distinct Ae. aegypti and characterized virus-derived sRNAs (vsRNAs). Overall, the distribution of total sRNAs was highly variable. Small RNAs derived from ISVs were diverse and dependent on geographic origin. We next infected Ae. aegypti from Poza Rica, Mexico with DENV2 and analyzed changes in the sRNA virome. DENV2 intrathoracic inoculation resulted in DENV2-specific siRNAs and piRNAs. We also found increased loads of sRNAs against the ISVs verdadero (Partitiviridae: unclassified), Aedes anphevirus (Xinmoviridae: Anphevirus), and chaq-like virus (Partitiviridae: unclassified) after DENV2 infection compared to ISV-derived sRNAs in controls. Overall, our study highlights the diversity of infective ISVs and the complexity of the sRNA virome across Ae. aegypti populations, which likely has consequences on sRNA crosstalk, virus replication, and vector competence. To gain insights on how Piwis, piRNA-binding proteins, are involved in virus control, we characterized structural features of an antiviral Piwi, Piwi4, involved in RNA binding and subcellular localization. We found that Piwi4 PAZ (Piwi/Argonaute/Zwille), the domain that binds the 3'-terminal ends of piRNAs, bound to mature (3'-terminal 2'-O-methylated) and 3'-terminal unmethylated RNAs with similar micromolar affinities (KD = 1.7 ± 0.8 μM and KD of 5.0 ± 2.2 μM, respectively) in a sequence independent manner. Through site-directed mutagenesis studies, we identified highly conserved residues involved in RNA binding and found that subtle changes in the amino acids flanking the binding pocket across PAZ proteins had significant impacts on binding behaviors, likely by impacting protein secondary structure. We also found that Piwi4 was both cytoplasmic and nuclear in mosquito tissues, and we identified a Piwi4 nuclear localization signal in the N-terminal region of the protein. These studies provide insights on the dynamic role of Piwi4 in RNAi and pave the way for future studies aimed at understanding Piwi4 interactions with diverse RNA populations.
Keywords: arbovirus; Piwi; Zika; mosquito; Aedes aegypti; RNA